Quasisymmetric (k,l)-hook Schur functions - Sarah Mason; Elizabeth Niese (Discrete Mathematics & Theoretical Computer Science, 2014)
We introduce a quasisymmetric generalization of Berele and Regev's hook Schur functions and prove that these new quasisymmetric hook Schur functions decompose the hook Schur functions in a natural way. In this paper we examine the combinatorics of the quasisymmetric hook Schur functions, providing analogues of the Robinson-Schensted-Knuth algorithm and a generalized Cauchy Identity.